Green(er) Cities and Their Citizens: Insights from the Participatory Budget of Lisbon - Falanga, Roberto (2021)
There is rising scholarly and political interest in participatory budgets and their potential to advance urban sustainability. This article aims to contribute to this field of study through the specific lens of the city of Lisbon’s experience as an internationally acknowledged leader in participatory budgeting. To this end, the article critically examines the lessons and potential contribution of the Lisbon Participatory Budget through a multimethod approach. Emerging trends and variations of citizen proposals, projects, votes, and public funding are analysed in tandem with emerging key topics that show links and trade-offs between locally embedded participation and the international discourse on urban sustainability. Our analysis reveals three interconnected findings: first, the achievements of the Lisbon Participatory Budget show the potential to counteract the dominant engineered approach to urban sustainability; second, trends and variations of the achievements depend on both citizens’ voice and the significant influence of the city council through policymaking; and, third, the shift towards a thematic Green Participatory Budget in 2020 was not driven by consolidated social and political awareness on the achievements, suggesting that more could be achieved through the 2021 urban sustainability oriented Participatory Budget. We conclude recommending that this kind of analysis should be systematically carried out and disseminated within city council departments, promoting much needed internal awareness of PBs’ potential as drivers of urban sustainability. We also identify further research needed into the sustainability potential of green PBs